THE CONCEPT OF SUSTAINABLE DEVELOPMENT AS A DRIVER OF THE FASHION SEGMENT TRANSFORMATION IN UKRAINE’S LIGHT INDUSTRY REGIONS - BUDNIKEVYCH, Iryna; HONCHAR, Vadym; LABIAK, Hanna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article explores the spatial transformation process of the fashion segment in Ukraine’s light industry regions under the concept of sustainable development. It reveals the impact of global challenges, including economic, social, environmental, and geopolitical factors, on the structure, functioning, and competitiveness of Ukraine’s fashion industry. Key aspects of the fashion segment’s development in the light industry are analyzed: the creation of environmentally responsible products, adaptation to international sustainability standards, carbon footprint reduction, and the development of local production using regional resources. The study highlights the regional characteristics defining the sector’s transformation priorities: environmental responsibility and craft production in the western regions, innovations and digitalization in the central regions, restoration of production capacities in the eastern regions, expansion of textile exports in the southern regions, and support for artisanal traditions in the northern regions. Each region has unique development prerequisites due to geographical, economic, and cultural factors. The western regions focus on creating eco-friendly and authentic products using local resources. The central regions are becoming innovation hubs through digital technology integration and startup support. The eastern regions emphasize restoring production capacities and creating jobs, while the southern regions focus on expanding textile production and exports through seaports. The northern regions prioritize artisanal traditions and cultural heritage. A model for adapting the fashion segment through the creation of regional clusters, the implementation of environmental standards, the development of socially responsible enterprises, and the formation of national brands in international markets is proposed. Special attention is paid to integrating national identity into fashion production, enhancing the competitive advantages of Ukrainian manufacturers. The research results can be used to develop regional development strategies and enhance the competitiveness of Ukrainian brands in the global market.